Investigation on breakdown voltage of TiO2 doped Al2O3 via spin coating method / Alyaa Ainaa Abdullah - Abdullah, Alyaa Ainaa (2018)
Thin films of TiO: doped AI2O3 were prepared by spin coating method on glass substrate. The main objectives of this project are to prepare the Ti02 doped AI2O3 thin films for measuring the breakdown voltage and to characterize the electrical, physical and optical properties Ti02 doped AI2O3 of thin films. Characterization of the thin films were carried out using different characterization techniques such as X-Ray diffraction (XRD), breakdown voltage and UV-Vis. Different percentages of Aluminum Oxide (AI2O3) in Ti02 were Oat%, 2at%, 4at%, 6at%, 8at% and 10at%. The thin films were annealed at 450°. The results show the breakdown voltage increased as the percentage of the atomic of AI2O3 increased. The XRD analysis of the thin films showed amorphous behaviors. The anatase phase transformation of TiO2 was formed as the thin films annealed at 450°. Further analysis on UV-Vis also has found that the percentage of transmittance of TiO2 doped AI2O3 increased as the percentage of atomic of AI2O3 increased In contrast to the transmittance spectrum, the percentage of absorbance of TiO2 doped AI2O3 was found to be decreasing with increasing of the percentage of atomic of AI2O3.